Synthesis of Ce–Ni/sepiolite with excellent adsorption and catalytic oxidation performance toward dyes. (10th January 2023) - Chen, Menglin; Wang, Lianying; Feng, Jinyu; Sun, Jiayue; Lin, Xiangfeng; Gao, Shu; Huang, Zhi; Su, Chengyuan; Wang, Liang
Abstract : A novel and highly efficient wastewater treatment process for the removal of industrial dyes was proposed in this study. Abstract : A novel and highly efficient wastewater treatment process for the removal of industrial dyes was proposed in this study. The method involved the regeneration of Ce–Ni/sepiolite, which acted as an adsorbent/catalyst, exhausted with the cationic dye auramine O (AO)—a frequently-used industrial dye—under a stream of O2 hot gas. The Ce–Ni/sepiolite adsorbent/catalyst was successfully synthesized by impregnation and was characterized by XRD, SEM, XPS, and BET techniques. An orthogonal experimental design method was applied to optimize the synthesis conditions of Ce–Ni/sepiolite. These synthesis conditions used the regeneration efficiency/rate of the catalyst as the evaluation index under heated O2 gas stream regeneration. Ce–Ni/sepiolite exhibited remarkable adsorption and catalytic oxidation degradation qualities for AO. The regeneration rate of as-prepared Ce–Ni/sepiolite reached 112.9% after 1 hour at 500 °C under 6 L min −1 of hot gas. The batch adsorption capacities were found to be 210.60 mg g −1 (25 °C), 243.90 mg g −1 (35 °C) and 263.16 mg g −1 (45 °C). 45 °C seemed to allow for the optimum adsorption capacity. Ce–Ni/sepiolite also showed high dynamic adsorption capacity, able to treat 48 bed volume (BV) of the dye solution with a residual concentration of 0 mg L −1 when the height to diameter ratio is 2.5. The adsorption and regeneration mechanisms were proposed. The as-synthesized Ce–Ni/sepiolite can be used as an efficient adsorbent and catalyst in wastewater treatments. This further supports the prospective usability of the sepiolite adsorbent for dye removal in future industrial applications.